2018
DOI: 10.3389/fmicb.2018.00950
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic Resistance Mediated by the MacB ABC Transporter Family: A Structural and Functional Perspective

Abstract: The MacB ABC transporter forms a tripartite efflux pump with the MacA adaptor protein and TolC outer membrane exit duct to expel antibiotics and export virulence factors from Gram-negative bacteria. Here, we review recent structural and functional data on MacB and its homologs. MacB has a fold that is distinct from other structurally characterized ABC transporters and uses a unique molecular mechanism termed mechanotransmission. Unlike other bacterial ABC transporters, MacB does not transport substrates across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
122
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 143 publications
(238 reference statements)
2
122
0
5
Order By: Relevance
“…BceAB-type systems belong to the type VII ABC transporter superfamily, of which the Escherichia coli macrolide resistance transporter MacB is the paradigm example (22). MacB was recently shown to act according to a molecular bellows mechanism and expel its substrate from the periplasm across the outer membrane via the TolC exit duct by undergoing extensive conformational changes in its periplasmic domain (23).…”
Section: Resultsmentioning
confidence: 99%
“…BceAB-type systems belong to the type VII ABC transporter superfamily, of which the Escherichia coli macrolide resistance transporter MacB is the paradigm example (22). MacB was recently shown to act according to a molecular bellows mechanism and expel its substrate from the periplasm across the outer membrane via the TolC exit duct by undergoing extensive conformational changes in its periplasmic domain (23).…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the roles of the MacB in bacterial physiology is becoming an important issue. 24 In this study, we reported OU33858, an inhibitor of MacAB in Salmonella. This compound might be useful for the functional analysis of this efflux pump, including its role in bacterial physiology and drug resistance.…”
Section: Discussionmentioning
confidence: 71%
“…MacAB contributes to both drug‐resistant and virulent phenotypes in many Gram‐negative bacteria, including pathogenic species 24 . These pumps drive not only the efflux of macrolide antibiotics but also the transport of heat‐stable enterotoxin II, outer membrane glycolipids, lipopeptides, and protoporphyrin 25–28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations